Pathological changes in experimentally induced astragalus cephalotes toxicity in mice - Yuksel, Hayati; Karadas, Erkan; Yaman, Ihsan; Cevik, Aydin (My University, 2009)
In this study, an experimental toxicity was induced in SWR - Swiss white mice by feeding standard pellets supplemented with Astragalus cephalotes. Clinically, lethargy, tremors, sudden jerks in response to stimuli, loss of weight and decreased birth rate were observed. Macroscopically, there was yellowish gel - like fluid within the abdomen in all the treated ES and ER groups. White focal areas 1-2 mm diameter were observed in the liver of the treated mice in the 15 and 20% ES and ER group. There were vacuolations in the parenchyma cells of the liver, kidneys and pancreas as well as congestion and haemorrhages in the lungs and heart. In addition, there was focal coagulation necrosis and perivascular lymphocyte infiltrations in the liver and perivascular and periglomerular lymphocyte infiltrations in the kidneys of the 15 and 20% ES and ER groups. It was observed that A. cephalotes sprouts were more toxic than A. cephalotes roots.
Keywords: Astragalus cephalotes; Mus